Freedom of Thought - Müge Akbulut (Türk Kütüphaneciliği)
In this editorial, the editors state that this issue has been prepared as a special issue on freedom of thought dedicated to Zafer Kızılkan, the chairperson of the Turkish Librarianship Association Freedom of Thought Group who passed away in 2014. Information is provided about the professional background of Kızılkan. In addition, notice is given that the journal Turkish Librarianship has now begun to be indexed in Web of Science Emerging Source Citation Index.